TANGGUNG JAWAB DOKTER TERHADAP PASIEN DALAM HAL TERJADINYA MALPRAKTIK MEDIK DILIHAT DARI PERSPEKTIF HUKUM PERDATA - Resfina Agustin Riza (STIH Putri Maharaja, 2018)
A doctor are obligated to do their duty with his or her ability and responsibility. However, doctor also make mistake because of neglect. The mistake in serving the patient is called medical malpractice. Their mistakes or negligence bring harm to the patient. Example is a case that happened to M S in Medan, North Sumatera. She came to the gynaecologist to treat her disease. Because the mistake of the doctors in surgery, the patient became disable for the rest of her life. The problems in this research is How the relationship between doctor and patient in a medical action according to the civil law? How is the responsibility of the doctors to the patient in medical malpractice action as case?. the writer used juridical normative method. The research done by the writer resulted in doctor and patient relationship in civil law point of view, which is the bonded relationship between medical service as the medical act between the provider of medical services with the receiver. The civil law responsibility of the doctor in case of medical malpractice comes from two basic law they are the responsibility as a doctor and the responsibility against law.